Steam Engine Bertha at Levens Hall - Gale, John (National Fairground Archive, University of Sheffield Library, 2001)
Preserved Fowler showman's road locomotive steam traction engine No.15116 'Bertha', registration 'CB3062' (built 1920) from the Levens Hall Steam collection circa 1965.